Novel Loss-of-Function Mutations in DNAH1 Displayed Different Phenotypic Spectrum in Humans and Mice - Khan, Ranjha; Zaman, Qumar; Chen, Jing; Khan, Manan; Ma, Ao; Zhou, Jianteng; Zhang, Beibei; Ali, Asim; Naeem, Muhammad; Zubair, Muhammad; Zhao, Daren; Shah, Wasim; et al. (Frontiers in Endocrinology, 2021)
Male infertility is a prevalent disorder distressing an estimated 70 million people worldwide. Despite continued progress in understanding the causes of male infertility, idiopathic sperm abnormalities such as multiple morphological abnormalities of sperm flagella (MMAF) still account for about 30% of male infertility. Recurrent mutations in DNAH1 have been reported to cause MMAF in various populations, but the underlying mechanism is still poorly explored. This study investigated the MMAF phenotype of two extended consanguineous Pakistani families without manifesting primary ciliary dyskinesia symptoms. The transmission electron microscopy analysis of cross-sections of microtubule doublets revealed a missing central singlet of microtubules and a disorganized fibrous sheath. SPAG6 staining, a marker generally used to check the integration of microtubules of central pair, further confirmed the disruption of central pair in the spermatozoa of patients. Thus, whole-exome sequencing (WES) was performed, and WES analysis identified two novel mutations in the DNAH1 gene that were recessively co-segregating with MMAF phenotype in both families. To mechanistically study the impact of identified mutation, we generated Dnah1 mice models to confirm the in vivo effects of identified mutations. Though Dnah1△iso1/△iso1 mutant mice represented MMAF phenotype, no significant defects were observed in the ultrastructure of mutant mice spermatozoa. Interestingly, we found DNAH1 isoform2 in Dnah1△iso1/△iso1 mutant mice that may be mediating the formation of normal ultrastructure in the absence of full-length protein. Altogether we are first reporting the possible explanation of inconsistency between mouse and human DNAH1 mutant phenotypes, which will pave the way for further understanding of the underlying pathophysiological mechanism of MMAF.